Pembelajaran daring materi luas segitiga dengan menggunakan pendekatan berbasis masalah terhadap kemampuan komunikasi matematis pada siswa kelas IV SD Negeri Jaya Giri - Eka Mustika Sari; Sukma Murni; Uus Kuswendi (COLLASE (Creative of Learning Students Elementary Education), 2025)
The mathematical communication ability of students in solving online learning problems with triangle area is one of the problems that are discussed in this study. This research was conducted to find out how the application of a problem based approachÂ  to mathematical communication skills in triangle area material. The method used in this research is descriptive qualitative, through this method the researcher tries to describe the situation and process in learning activities. The subjects in this study were fourth grade students of SD Negeri Jaya Giri in the city of Ngamprah. From the results of the study that fourth grade students were happy with online learning of triangle area material using a problem basedÂ  approach , besides that students and teachers showed positive responses to online learning of triangle area material using a problem based approach , but still found students who have difficulty in solving online learning problems with triangle area material on mathematical communication indicators make conjectures, develop arguments, formulate definitions, and generalize. From this discussion, it can be concluded that the mathematical communication ability of triangle material on the indicators of mathematical communication to make conjectures, construct arguments, formulate definitions, and generalizations is low and needs to be given routine practice questions so that students are accustomed to solving difficult questions.